Designing luminescent ruthenium prodrug for precise cancer therapy and rapid clinical diagnosis. (February 2019) - Zhao, Zhennan; Zhang, Xiang; Li, Chang-e; Chen, Tianfeng
Abstract: The effective design of a targeted drug delivery system could improve the therapeutic efficacy of anticancer drugs by reducing their undesirable adsorption and toxic side effects. Here, an RGD-peptide functionalized and bioresponsive ruthenium prodrug (Ru-RGD ) was designed for both cancer therapy and clinical diagnosis. This prodrug can be selectively delivered to cervical tumor sites to enhance theranostic efficacy. The benzimidazole-based ligand of the complex is susceptible to acidic conditions so, after reaching the tumor microenvironment, ligand substitution occurs and the therapeutic drug is released. The deep-red emissions produced by both one-photon and two-photon excitation increases the potential of Ru-RGD for use in the deep tissue imaging of 3D tumor spheroids. The specific accumulation of the Ru prodrug in tumor sites allows for precise tumor diagnosis and therapy in vivo . Luminescence staining of 38 clinical patient specimens shows that Ru-RGD exhibits differences in binding capability between cervical cancer and normal tissue, with a sensitivity of 95% and a specificity of 100%. This study thus provides an approach for the effective design and application of targeted metal complexes in cancer therapy and clinical diagnosis. Graphical abstract: A bioresponsive prodrug was designed to realize precise cancer therapy and rapid clinical diagnosis. The RGD-peptide functionalized Ru prodrug (Ru-RGD) could be selectively delivered to the tumor microenvironment, where it is designed to release the therapeutic drug. The deep-red luminescence of this complex makes it suitable for in vivo tumor imaging and specific luminescence staining of clinical specimens from patients, demonstrating the theranostic potential of these complexes. Image 1